Public opinions on disclosure of tobacco components: Results of a nationwide cross-sectional survey in Republic of Korea. Issue 27 (July 2016) - Yun, E Hwa; Park, Young-Ok; Lim, Min Kyung; Oh, Jin-Kyoung; Park, Eun Young; Jeong, Bo Yoon; Hong, Soon-Yeol; Lee, Do-Hoon
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This study aimed to explore public views on disclosure of tobacco components in an effort to develop a comprehensive regulatory system facilitating implementation of the Framework Convention on Tobacco Control (FCTC) Articles 9 and 10 in Korea. In all, 1200 representative Koreans 19 years old or older were enrolled and information on their general characteristics, smoking status, awareness of the effects of smoking on health, and views on the public disclosure of tobacco components was collected by telephone using a structured questionnaire. Factors associated with acceptance of the need for public disclosure of tobacco components were identified via multivariate analysis. Most participants considered it necessary to publicly disclose tobacco components (95.9%) and were aware of the risk to health posed by smoking (76.0%). The prevalent view was that tobacco companies should be legally required to publicly disclose details of the components of cigarettes, their levels per cigarette, and their effects on health. The most effective means of disclosure were considered to be the mass media, printed materials, and labels on cigarette packs. Females and never-smokers (odds ratio [OR]: 4.39, 95% confidence interval [95% CI]: 1.76–10.94) more readily accepted the need for public disclosure, whereas those of lower educational level and/or who were less aware of the harm to health posed by smoking (OR: 0.05, 95% CI: 0.01–0.18) were less likely to be accepting. The attitude of the general population ensures that FCTC Articles 9 and 10 will be successfully implemented in Korea. Further public consultation on the details of disclosure would be useful for the development of a comprehensive regulatory system.